Effect of Different Milk Diet on the Level of Fecal Calprotectin in Very Preterm Infants - Costa, Simonetta; Patti, Maria Letizia; Perri, Alessandro; Cocca, Carmen; Pinna, Giovanni; Tirone, Chiara; Tana, Milena; Lio, Alessandra; Vento, Giovanni (Frontiers in Pediatrics, 2020)
Objective: To evaluate the course of fecal calprotectin (FC) in very preterm infants over the first 15 days of life in relation to the type of milk diet. Methods: This study was part of a randomized controlled trial, comparing two different ways of integrating the own mother’s milk (OMM) for the evaluation of feeding tolerance in very preterm infants. In infants with gestational age of ≤32 weeks, randomized to receive preterm formula (PF group) or pasteurized donor human milk (PDHM group) as a supplement to the OMM insufficient or unavailable, FC level was planned to be measured at the first meconium passage, and at day 8 and 15 of life (T0, T1 and T2, respectively). Results: FC data were available for all the 70 infants randomized, 35 in the PF group and 35 in the PDHM group. The mean FC levels were similar in the two study groups at T0 and T1, whereas they were significantly higher in PF group than the PDHM group at T2. FC values decreased over the first week of life in both groups, and significantly increased over the second week of life only in the PF group. Conclusions: Our study demonstrates a significant increase in FC levels when PF is used as a supplement to the OMM, compared to the use of PDHM. Further studies are needed to establish if the higher FC levels in infants receiving PF are the expression of a normal immunological maturation rather than an initial inflammatory process.